Clouds and Radiation in a Mock‐Walker Circulation. (2nd February 2021) - Silvers, Levi G.; Robinson, Thomas
Abstract: The Walker circulation connects the regions with deep atmospheric convection in the western tropical Pacific to the shallow‐convection, tropospheric subsidence, and stratocumulus cloud decks of the eastern Pacific. The purpose of this study is to better understand the multi‐scale interactions between the Walker circulation, cloud systems, and interactive radiation. To do this we simulate a mock‐Walker Circulation with a full‐physics general circulation model using idealized boundary conditions. Our experiments use a doubly‐periodic domain with grid‐spacing of 1, 2, 25, and 100 km. We thus span the range from General Circulation Models (GCMs) to Cloud‐system Resolving Models (CRMs). Our model is derived from the Geophysical Fluid Dynamics Laboratory atmospheric GCM (AM4.0). We find substantial differences in the mock‐Walker circulation simulated by our GCM‐like and CRM‐like experiments. The CRM‐like experiments have more upper level clouds, stronger overturning circulations, and less precipitation. The GCM‐like experiments have a low‐level cloud fraction that is up to 20% larger. These differences leads to opposite atmospheric responses to changes in the longwave cloud radiative effect (LWCRE). Active LWCRE leads to increased precipitation for our GCMs, but decreased precipitation for our CRMs. The LWCRE leads to a narrower rising branch of the circulation and substantially increases the fraction of precipitation from the large‐scale cloud parameterization. This work demonstrates that a mock‐Walker circulation is a useful generalization of radiative convective equilibrium that includes a large‐scale circulation. Plain Language Summary: Interactions between clouds, radiation, and dynamics all contribute to the large‐scale tropical motions and are fundamental to the Walker circulation. The Walker circulation is a loop consisting of surface winds toward the western tropical Pacific, strong upward motion and deep convection in that region, and the return eastward winds aloft that eventually sink toward the surface in the eastern Pacific basin. We focus on an idealization of the Walker circulation (a mock‐Walker circulation) in which the strong rising motion and deep convection is driven by a patch of warm sea surface temperature. Our results show that the response of the atmosphere to the radiative flux of energy depends strongly on the relative amount of clouds at different heights. It is further shown that our GCM‐like models are dominated by low‐clouds while our CRM‐like models are dominated by high‐clouds. This work also argues that an idealized Walker circulation is an excellent configuration with which to better understand the interactions between clouds, radiation, and circulation and to push the development of models forward. Models of mock‐Walker circulations represent an intermediate tier in a hierarchy of models between Earth‐like models and models of radiative convective equilibrium. Key Points: These cloud resolving simulations result in more upper‐level clouds, relative to low resolution simulations that have more low‐level clouds High and low clouds interact differently with longwave radiation to increase or decrease precipitation, depending on the dominant cloud type Interactions between clouds and radiation combined with parameterized convection shift the precipitation maximum away from the sea surface temperature maximum